Peningkatan Motivasi dan Interpretasi Diagram Pencar melalui PBL Berbantuan Microsoft Excel - Gita Adelia Pratiwi; Lady Agustina; Niswati Amin (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
Through the implementation of Problem-Based Learning (PBL) supported by Microsoft Excel, this study sought to strengthen students’ learning motivation and improve their ability to create and interpret scatter plots. The research employed Classroom Action Research conducted in two cycles involving eleventh-grade students of SMA Muhammadiyah 1 Rambipuji. Data were collected via motivation questionnaires, tests, observations, and documentation. Results showed the average motivation score increased from 55 (low) in the pre-cycle to 67 (high) in Cycle I, and 81 (very high) in Cycle II. The average learning score improved from 32.1 to 68.6 in Cycle I and 80.0 in Cycle II, reaching a 71.43% mastery rate. Excel’s Scatter Plot feature simplified data visualization and reduced manual computation, allowing students to focus on data analysis. Therefore, Problem-Based Learning assisted by Microsoft Excel was effective in improving students’ learning motivation and their ability to construct and interpret scatter plots. Keywords: Learning Motivation, Scatter Plot, Problem-Based Learning, Microsoft Excel